A new gas/supercritical fluid (SCF) diffusivity measurement method for CO2 saturated polymer systems using a dielectric property - S. X. Yao; P. C. Lee (eXPRESS Polymer Letters, 2017)
In this research, theoretical CO2 diffusivity coefficients in amorphous polymers were calculated from dielectric constant changes during CO2 desorption. These values showed agreement with experimental diffusivity coefficients from a gravimetric method. Three amorphous polymer films made from Polystyrene (PS), Polycarbonate (PC), and Cyclic Olefin Polymer (COP) resins were saturated with supercritical CO2 at 5.5 MPa and 25 °C for 24 hours in a pressure chamber. The CO2 infused films were removed from the chamber for gas desorption experiments. The capacitance of the samples were recorded with an Inductance, Capacitance and Resistance (LCR) meter. These values were used to calculate the change in dielectric constants. CO2 weight percentages measured by a scale was used to calculate experimental diffusivity and solubility coefficients. It was found that the trend of dielectric constant changes was similar to that of the CO2 weight percentage changes during gas desorption. A mathematical model was built to predict the CO2 weight percentages during desorption from the measured dielectric constants. Theoretical diffusivity coefficients from this work agree well with literature data.